Instrumentalization of the Venezuelan migration in the presidential elections of Colombia (2018) and Peru (2021). A critical discourse analysis - Valera Marin, Aymara M. (2023)
This study analyzes the instrumentalization of the Venezuelan migration in the presidential elections of Colombia (2018) and Peru (2021), through a critical discourse analysis (CDA). This research shows the importance of the linguistic and discursive aspects in policies and politics. In addition, it was clear that the Venezuelan migration was used for the construction of political and xenophobic discourses manipulated by the presidential candidates and the media as a topic of interest for the presidential elections of Colombia and Peru.